2017
DOI: 10.5334/tohm.381
|View full text |Cite
|
Sign up to set email alerts
|

Speech–Language Pathology Evaluation and Management of Hyperkinetic Disorders Affecting Speech and Swallowing Function

Abstract: Background: Hyperkinetic dysarthria is characterized by abnormal involuntary movements affecting respiratory, phonatory, and articulatory structures impacting speech and deglutition. Speech-language pathologists (SLPs) play an important role in the evaluation and management of dysarthria and dysphagia. This review describes the standard clinical evaluation and treatment approaches by SLPs for addressing impaired speech and deglutition in specific hyperkinetic dysarthria populations. Methods: A literature revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 80 publications
(184 reference statements)
1
17
0
2
Order By: Relevance
“…Phono-articulatory changes in dystonia patients are generally classified as hyperkinetic dysarthrophonia 18 , 20 - 22 . In our study, complaints of voice changes were observed in 55.6% of study subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phono-articulatory changes in dystonia patients are generally classified as hyperkinetic dysarthrophonia 18 , 20 - 22 . In our study, complaints of voice changes were observed in 55.6% of study subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, interruption of the continuous airflow for sustained vocalization can also promote constant breaks in sonority, thus affecting the intelligibility and quality of communication. However, variations in pitch or loudness, inappropriate pauses, hyper or hyponasality, articulatory inaccuracy, and reduced speech rate are characteristic of hyperkinetic dysarthrophonia 18 , 22 - 25 . Although dysarthrophonia is apparently unrelated to swallowing changes, they maintain a close relationship because the same muscles are involved in these two vital functions.…”
Section: Discussionmentioning
confidence: 99%
“…Bei einer Dysarthrophonie sollte die Selbsteinschätzung des Patienten im Hinblick auf die Auswirkung des beeinträchtigten Sprechens auf den Alltag routinemäßig erfasst werden [39]. Bei Morbus Parkinson können schon leichte Dysarthrophonien zu negativen Einstellungen, gar zu Diskriminierungen durch Kommunikationspartner führen [40]. Patienten mit Morbus Parkinson, die ihre Sprachverständlichkeit schlechter einschätzten, gaben auch eine geringere Lebensqualität an [41,42].…”
Section: Dysarthrophonieunclassified
“…Two types of palatal myoclonus have been described: a symptomatic form attributable to a pathologic lesion involving the brainstem or cerebellum often identified on MRI imaging, and an essential form without an identifiable structural cause [2]. Palato-pharyngo-laryngeal myoclonus is a rare variant of palatal myoclonus affecting not only the palate but the pharynx and larynx as well, which may result in dysphagia, dysphonia, and dysarthria [3][4][5]. Upon review of the current literature, there are minimal, if any, gastrointestinal (GI) symptoms reported by patients with this condition.…”
Section: Introductionmentioning
confidence: 99%